Quantitative Linguistic Predictors of Infants' Learning of Specific English Words. Issue 4 (1st February 2017) - Swingley, Daniel; Humphrey, Colman
Abstract : To evaluate which features of spoken language aid infant word learning, a corpus of infant‐directed speech (M. R. Brent & J. M. Siskind, 2001) was characterized on several linguistic dimensions and statistically related to the infants' vocabulary outcomes word by word. Comprehension (at 12 and 15 months) and production (15 months) were predicted by frequency, frequency of occurrence in one‐word utterances, concreteness, utterance length, and typical duration. These features have been proposed to influence learning before, but here their relative contributions were measured. Mothers' data predicted learning in their own children better than in other children; thus, vocabulary is measurably aligned within families. These analyses provide a quantitative basis for claims concerning the relevance of several properties of maternal English speech in facilitating early word learning.